Exploring the effectiveness of benson relaxation technique in group counselling to reduce public speaking anxiety of junior high school students - Istati, Mufida; Aila, Syifa Nur (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study explores the effectiveness of Benson relaxation technique in group counselling to reduce public speaking anxiety in students. The research design used is pre-experimental with a one-group pretest-posttest model. The sample consisted of five junior high school students in Banjar Regency, South Kalimantan, who were purposively selected because they had very high levels of anxiety. The sample was selected through purposive sampling based on criteria that indicated very high levels of public speaking anxiety, as measured by the public speaking anxiety scale. The intervention was group counselling for four sessions with Benson relaxation technique. Results showed a decrease in anxiety from very high to low. Paired T-test showed a significance value of 0.000 (<0.05), confirming the effectiveness of the intervention. The Benson relaxation technique, which has been scientifically proven to reduce anxiety responses through regular breathing and repetition of calming words. The findings support the theoretical framework that physiological relaxation can effectively reduce anxiety by activating the body's relaxation response. This research contributes to group counselling practice by offering the effectiveness of relaxation techniques supported by group dynamics.